Respon Sekolah Terhadap Program Adiwiyata Studi Kasus pada Sekolah Dasar di Kota Batu - Mardi Wiyono (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2008)
Abstract: The puspose of this research is to describe respons of schools to Adiwiyata program. This research is case study of elementary schools at Batu City. The research method is conducted by descriptive method. Indicators that reviewed is: management of school, implementation of enviromental educaton, and support facilities. Based on this research show that from three schools, SD Mojorejo 1, SD Sang Timur, and SD Tulungrejo 4, the best of prestation is SD Sang Timur.